Antioxidant Activity Test of Vanilla Leaf Kombucha Tea with Variations in Fermentation Time - Eva Agustina; Esti Tyastirin; Risa Purnamasari; Nova Lusiana; Funsu Andiarna (Jurnal Sains Dasar, 2025)
Kombucha tea is a fermented tea leaf drink with added sugar and Symbiotic Culture of Bacteria and Yeast (SCOBY). Vanilla leaves (Vanilla planifolia) have the potential to be the basic ingredient for making kombucha tea. Variations in fermentation time in tea making can affect the content of active compounds. The purpose of this study was to determine the levels of phenolic compounds and antioxidant activity of kombucha tea with variations in fermentation time. The fermentation time for making vanilla leaf kombucha tea is 0, 4, 8, and 12 days. The phenolic compounds were known by the Folin–Ciocalteu method using the gallic acid standard, while the antioxidant activity was known by the free radical inhibition method 2,2-diphenyl-1-pycrylhydrazyl (DPPH). The results showed that the levels of phenolic compounds at fermentation times of 0, 4, 8, and 12 days were 37.99, 42.188, 57.58, respectively, and 50.53 mg/L GAE. The highest phenolic levels are found at the 8th day of fermentation. The IC50 values for fermentation times of 0, 4, 8, and 12 consecutive days were 18%, 7.9%, 4%, and 7.7% v/v. An IC50 value < 50 indicates strong antioxidant activity. Vanilla leaf kombucha tea has the potential to be a beverage product that is beneficial for health due to its content of phenolic compounds and antioxidant activity.